Determination of beta-delayed neutron emission probability limits of rhodium isotopes by gamma-ray spectroscopy. (December 2020) - Shearman, R; Lorusso, G; Boso, A; Regan, P H; Nishimura, S; Xu, Z Y; Jungclaus, A; Shimizu, Y; Simpson, G S; Söderström, P-A; Watanabe, H; Browne, F; et al.
Abstract: The decay of five neutron-heavy rhodium isotopes were studied at the Radioactive Isotope Beam Factory (RIBF) Facility at the RIKEN Nishina Center after relativistic fission of 238 U beam on a thick beryllium target. Previously unknown associated gamma-ray decay energies are reported for each nuclide, and through evaluating the intensity of the 2 + → 0 + E2 transition in the even-even palladium daughter nuclei, 120, 122, 124 Pd, from the beta-tagged gamma-ray spectra an upper or lower limit of beta-delayed neutron emission is deduced for each nuclei. A general, expected trend of increasing Pn is observed in the direction of the neutron drip line.